Agronomic Performance of Spring‐Sown Faba Bean in Southeastern Washington. (1st March 2015) - Landry, Erik J.; Coyne, Clarice J.; Hu, Jinguo
Abstract : Faba bean ( Vicia faba L.) is the world's fourth most important cool‐season pulse crop. Currently commercial faba bean cultivars are unavailable in the United States specifically selected for grain production; therefore, a spring‐sown variety trial with 11 populations was conducted for two seasons at two contrasting locations in southeastern Washington. Early seeding was expected to achieve optimal grain yield. In 2012, the warmer Central Ferry, WA, location was sown a month earlier than at Pullman, WA (April vs. May), resulting in earlier flowering, higher grain yield, and an earlier maturity across populations. A drier March–April in 2013 allowed similar sowing dates across locations, synchronizing phenological development and improving grain yields at Pullman. However, at Central Ferry, yield was reduced due to high temperatures (>35°C) and subsequent flower and pod shedding. The National Plant Germplasm System (NPGS) accession W6 12023 and the Extra Precoce Violetto × Hiverna/2 F3 :5 breeding population were the highest yielding populations and earliest to flower and mature in 2012 and 2013, respectively. Across 4 site‐years, W6 12023 proved to have superior general adaptability with a high mean plant yield (22.6 g plant −1 ). Yield data compared favorably to other spring sown pulses currently grown in the region; therefore, a multi‐environment trial with early maturing spring‐type cultivars is warranted.